Clinical outcomes of conjunctivochalasis treatment with a new ophthalmic radiofrequency device - Kim, Bokyung; Lee, Yongwoo; Son, Hyeck Soo; Choi, Chul Young (BMC ophthalmology, 2024)
To investigate the safety and efficacy of a new micro-controlled radiofrequency device for treatment of conjunctivochalasis (Cch).
Gesehen am 14.01.2025